2019
DOI: 10.1136/archdischild-2019-316895
|View full text |Cite
|
Sign up to set email alerts
|

Demand for health services and drug prescriptions among overweight or obese preschool children

Abstract: ObjectivesTo evaluate the association between excess weight and the demand of health services in preschool children compared with healthy weight.MethodsThe data come from the Longitudinal Study of Childhood Obesity cohort (1884 4-year-old children, residing in the Madrid region, Spain) who provided information through telephone questionnaire, physical examination and electronic medical records. We defined overweight, general and abdominal obesity based on body mass index, waist circumference and waist-to-heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…One study analysed data collected as part of an established cohort study, 24 while the others made use of routinely collected health records. A total of 1 232 895 children were included in the four studies, with sample sizes ranging from 1844 children 24 to almost 600 000, 23 and follow-up from 2 24 to 13 years. 23 Of the studies reporting their study sample sex distribution, 51.4% of the sample were male.…”
Section: Resultsmentioning
confidence: 99%
“…One study analysed data collected as part of an established cohort study, 24 while the others made use of routinely collected health records. A total of 1 232 895 children were included in the four studies, with sample sizes ranging from 1844 children 24 to almost 600 000, 23 and follow-up from 2 24 to 13 years. 23 Of the studies reporting their study sample sex distribution, 51.4% of the sample were male.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported outcome measures were emergency department (ED) visits (n=10) 32–34 37–43 and outpatient (n=11) visits (including primary care and specialty visits). 32–34 36–41 43 44 Seven studies reported on healthcare use associated with respiratory diseases, 41 44–49 two reported on musculoskeletal conditions 44 50 and two on conditions concerning mental health. 37 44 The rest of the studies analysed the overall healthcare use in children with no reporting on reasons for utilisation.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported a non-significant decrease in admissions. 44 56 In addition, one study reported that 14.5% of obese or overweight children were admitted, compared with 16.5% normal-weight children. 42 For overweight children, one study reported a significant decrease 56 while one reported a non-significant decrease 37 in admissions compared with normal-weight children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations